A Study on English Reading Comprehension Difficulties in the Context of ESP: A Case of Fish Processing Technology Students - Ula, Radhiyatul; Mubin, Mubin; Hendriyani, Hendriyani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Reading comprehension is a crucial skill that should be mastered by students in English for Specific Purposes (ESP) where access to updated scientific information often requires a proper understanding of English texts. This research aimed at investigating the difficulties faced by Fish Processing Technology students in comprehending English reading texts which are relevant to their field. This was quantitative descriptive research where the data were collected through questionnaires and worksheets involving 20 second semester students. The research results show that 100% of the students have a lack of attention. Their focus is easily distracted while reading a text, especially English texts. Next, 95% of the students have limited knowledge of generic structure. They cannot understand the text's meaning because they do not know how to translate it grammatically. After that, 85% of the students faced difficulties in extracting the text meaning because of their lack of vocabulary mastery. They get a lot of unfamiliar words in the texts. Then, 75% of the students find obstacles in understanding the meaning of the text because they have no background knowledge about the text topic. 55% of the students have no motivation in reading, especially English texts. 50% of the students have limited working memories. Therefore, the researcher concluded that there are seven difficulties faced by the students, named attention, knowledge of generic structure, vocabulary, sentence comprehension, background of knowledge, motivation and working memory